Antigenicity and Immunogenicity of Salmonella enteritidis: Its Implication for Diagnosis and Development of Local Isolate Vaccine for Poultry - Ariyanti, Tati; ., Supar (Indonesian Animal Sciences Society, 2008)
Genus Salmonella consists of more than 2,400 serovars, which can be identified by means of serological method based on the variation of their somatic (O), flagellar (H) and capsular antigens (Vi). Salmonella serovars which are able to cause disease in animal or domestic animal are limited, such as: S. pullorum and S. gallinarum which are well adapted to poultry, cause fowl typhoid, S. cholerasuis causes disease in swine. S. typhimurium and S. enteritidis can infect all animals and humans. S. typhimurium and S. enteritidis could be isolated from salmonellosis of poultry, meat, milk and eggs. The prevalence of those isolates within the last two decades tends to increase. Pathogenic Salmonella serovars can infect both animals and humans, colonize the intestinal epithelial cells lead to diarrhoea. Salmonella spp. may enter the lower layer of epithelial cells and the lymphoid vascular system. Humoral antibody and cell mediated immunity responses may develop. Extraintestinal shedding or dissemination of Salmonella spp. may occur and multiply, this may cause latent infections and spread to the environment. Serologic diagnosis of infected animals can be done by means of serum or whole blood agglutination tests with whole cell antigen or ELISA with LPS coated tray, might demonstrate cross reactions among serovars within the one group. ELISA antibody by using fimbrial SEF14 antigen demonstrated specific diagnosis of S. enteritidis infection. The use of S. enteritidis inactive vaccines stimulates high humoral antibody response and protection against challenged homologous serovar within one group (D). The secretory antibody in mucosal surface of intestine and cell mediated immunity were not stimulated after vaccination with inactive Salmonella vaccine. Inactive vaccines (local isolate of S. enteritidis) which was developed and evaluated on experimental layer chicken produced protection against challenged homologous and may be used to control vertical transmission salmonellosis through eggs and can be used to improve the safety of animal food products for human consumption. Key words: Salmonella enteritidis, antigenicity, immunogenicity, diagnosis, vaccines for poultry